2020
DOI: 10.5614/sostek.itbj.2020.19.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Its Determinants: Preliminary Findings Among Lecturers in an Indonesian University

Abstract: The educational institution is sometimes indicated as a not attractive workplace, which could affect its employee happiness. This research aims to qualitatively identify the state of happiness and its determinants factors including its association with digital technology among lecturers. Digital technology is considered important in the educational area because it helps lecturers to effectively share the information, material, and managing the class. The research was conducted in ITB since it was a university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The interconnects between personnel welfare and the happiness index can be seen through its importance for the mental stability of the personnel. As demonstrated by Ginting et al (2020), motivation among teaching personnel is important for increasing their positive outlook toward the workplace. Additionally, training programs are conclusive for intensifying their skills in teaching students along with escalating their management capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The interconnects between personnel welfare and the happiness index can be seen through its importance for the mental stability of the personnel. As demonstrated by Ginting et al (2020), motivation among teaching personnel is important for increasing their positive outlook toward the workplace. Additionally, training programs are conclusive for intensifying their skills in teaching students along with escalating their management capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…La predicción antes referida pasó de ser un avance progresivo a un cambio radical intempestivo Al respecto, algunas investigaciones refieren que un indicador que conduce al incremento de desempeño laboral frente a los entornos virtuales, es la aceptación de la tecnología, además de la satisfacción, conocimiento, habilidades, actitudes y clima laboral (Bangun et al, 2021;Ginting et al, 2020;Hsiao & Lin, 2018); representando la tecnología un potencial significativo para la educación online y un antecedente sólido para ampliar los servicios de educación (Alabdulaziz, 2021). Es bueno resaltar, que durante los primeros días de la pandemia, la tecnología direccionada a la formación académica fue rechazada por los estudiantes, generándoles en primera instancia, insatisfacción hacia las clases online y un serio impacto en el aprendizaje (Bader et al, 2021).…”
unclassified
“…Second variable has been added as a mediator which is the job satisfaction among the relationship between digital transformation and job performance. As mentioned earlier, Digital technology is implicitly related to increased happiness, and happier individuals work much harder (Ginting et al, 2020). Hence, this has gone from a partial to a full mediation.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies have demonstrated a positive correlation between attitudes toward change and work satisfaction (Cordery et al, 1993;Iverson, 1996). Ginting et al (2020) assert that digital technology has a significant impact on happiness. Depending on one's attitude toward digital technology, employment satisfaction, which is a happy or positive emotional state resulting from the appraisal of one's job and work experiences, may be connected to happiness (Tang et al, 2019).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation